Particle Swarm Based Approach of a Real-Time Discrete Neural Identifier for Linear Induction Motors. (29th December 2013) - Alanis, Alma Y.; Rangel, E.; Rivera, J.; Arana-Daniel, N.; Lopez-Franco, C.
Abstract : This paper focusses on a discrete-time neural identifier applied to a linear induction motor (LIM) model, whose model is assumed to be unknown. This neural identifier is robust in presence of external and internal uncertainties. The proposed scheme is based on a discrete-time recurrent high-order neural network (RHONN) trained with a novel algorithm based on extended Kalman filter (EKF) and particle swarm optimization (PSO), using an online series-parallel con figuration. Real-time results are included in order to illustrate the applicability of the proposed scheme.